2017 European guideline for the screening, prevention and initial management of hepatitis B and C infections in sexual health settings. (September 2018) - Brook, Gary; Brockmeyer, Norbert; van de Laar, Thijs; Schellberg, Sven; Winter, Andrew J
This guideline updates the 2010 European guideline for the management of hepatitis B and C virus infections. It is primarily intended to provide advice on testing, prevention and initial management of viral hepatitis B and C for clinicians working in sexual health clinical settings in European countries. The guideline is in a new question and answer format based on clinical situations, from which population/intervention/comparison/outcome questions were formulated. Updates cover areas such as epidemiology, point-of-care tests for hepatitis B, hepatitis C risk and 'chemsex', and HIV pre-exposure prophylaxis and hepatitis B. We have also included a short paragraph on hepatitis E noting there is no evidence for sexual transmission. The guideline has been prepared in accordance with the Europe protocol for production available athttp://www.iusti.org/regions/europe/pdf/2017/ProtocolForProduction2017.pdf